Flavonoids Regulate Inflammation and Oxidative Stress in Cancer - Guangxing Li; Kaiyue Ding; Yanling Qiao; Liu Zhang; Luping Zheng; Taowen Pan; Lin Zhang (Molecules, 2020)
Cancer is the second leading cause of death globally. Millions of persons die due to cancer each year. In the last two decades, the anticancer effects of natural flavonoids have become a hot topic in many laboratories. Meanwhile, flavonoids, of which over 8000 molecules are known to date, are potential candidates for the discovery of anticancer drugs. The current review summarizes the major flavonoid classes of anticancer efficacy and discusses the potential anti-cancer mechanisms through inflammation and oxidative stress action, which were based on database and clinical studies within the past years. The results showed that flavonoids could regulate the inflammatory response and oxidative stress of tumor through some anti-inflammatory mechanisms such as NF-κB, so as to realize the anti-tumor effect.